Свойства ультрамелкозернистого композита Cu—64WC, полученного вакуумным горячим прессованием - Лаптев, А.В.; Толочин, А.И.; Крячко, Л.А.; Вербило, Д.Г.; Окунь, И.Ю. (Электрические контакты и электроды, 2010)
Ультрамелкозернистая смесь порошков карбида вольфрама и меди с объемным содержанием карбида вольфрама 50% (64% (мас.)) приготовлена интенсивным размолом в шаровом барабане с твердосплавными шарами. Горячее прессование с высоким давлением обеспечивает получение высокой плотности 92% при температуре 750 оС, в то время как жидкофазное спекание при 1150 оС в течение 20 мин приводит к плотности 88%. Высокий уровень механических свойств достигается при уплотнении горячим прессованием в области темпе-ратуры 1050 оС: пределы прочности при изгибе и сжатии — 1800 ± 80 и 1970 ± 260 МПа соответственно, твердость HV10 — 3840 ± 290 МПа. При этом сохраняется ультрамелкозернистая структура (размер частиц WС — 0,3—0,5 мкм). Ультрадрібнозерниста суміш порошків карбіду вольфраму і міді з об’ємним вмістом карбіду вольфраму 50% (64% (мас.)) виготовлена інтенсивним помелом в кульовому барабані з твердосплавними кулями. Гаряче пресування з високим тиском забезпечує отримання високої густини 92% при температурі 750 оС, тоді як рідкофазне спікання при 1150 оС протягом 20 хв приводить до густини 88%. Високий рівень механічних властивостей досягається при ущільненні гарячим пресуванням в області температури 1050 оС: границі міцності при вигині та стисненні — 1800 ± 80 і 1970 ± 260 МПа відповідно, твердість HV10 — 3840 ± 290 МПа. При цьому зберігається ультрадрібнозерниста структура (розмір частинок WС — 0,3—0,5 мкм). Ultrafine mixture of tungsten carbide and copper powders with volume fraction of tungsten carbide 50% (64% (wt.)) was prepared by the intensive grinding in a ball drum with hard-alloy balls. After grinding one part of mixture was kept on air, and second processed hydrogen at 400 оC during 2 hours. The densification in a vacuum to one and to other part of mixture at different temperatures and at the use of two methods — ordinary sintering and hot-pressed under pressure 1000–-1200 MPa was investigated. It is find out that heating of raw preforms from ultrafine mixture in a vacuum allows to get high-quality specimens even from more oxidized mixture and level the role of mixture hydrogen rough-down, decreasing the initial oxygen content. The hot pressing with the high level of pressure provides the obtaining of high-density, 92%, at the temperature of 750 oС, while the liquid sintering at 1150 oС during 20 min results in the relative density 88%. However, high-dense specimens obtaining at a low temperature possess lowered conductivity and mechanical properties, presumably, from low quality of boundaries. The high level of mechanical properties is achieved at the hot pressing densification in area of temperature of 1050 oС. At the indicated densification temperature this composite has a ultrafine structure (size of WС particles 0,3—0,5 μk) and followings mechanical properties: transverse rupture strength — 1800 ± 80 MPa, compression strength — 1970 ± 260 МPа, HV10 hardness — 3840 ± 290 MPa.